QUALITY OF SERVICE PROVISIONING USING MULTICRITERIA HANDOVER STRATEGY IN OVERLAID NETWORKS - Deswal, Suman; Singhrova, Anita (Malaysian Journal of Computer Science, 2020)
The poor coverage problem inside the buildings and the existence of disparate wireless technologies have led to the development of integrated macro femtocellular networks. Correct and efficient vertical handover decision is of utmost importance in such integrated macro femtocellular networks. Initially, Received Signal Strength (RSS) used to be the sole criterion for taking a decision for vertical handover. Such decision leads to inaccurate results and therefore unnecessary handovers. In this paper, a multicriteria vertical handover strategy based on received signal strength, user velocity, number of users in a cell and data rate of the cell is proposed. This proposed strategy and the traditional algorithm are simulated and the results are analyzed quantitatively for different QoS parameters namely ping pong rate, packet loss ratio, throughput, packet delay, jitter and signalling cost. The results show significant improvement in the QoS parameters when the proposed strategy is used as compared to traditional algorithm.